Robust dynamic positioning of surface vessels via multiple unidirectional tugboats - Bidikli, Baris; Tatlıcıoğlu, Enver; Zergeroğlu, Erkan (Pergamon-Elsevier Science Ltd, 2016)
In this paper, the problem of accurate positioning of an unactuated surface vessel by using multiple unidirectional tugboats is investigated. Specifically a robust controller that ensures asymptotic position tracking is designed. The control design procedure is implemented in two steps: Initially by locating opposing tugboats to specific configurations, the overall problem is transformed into a second order system with an uncertain non-symmetric input gain matrix. Then via a matrix decomposition, a novel robust controller methodology is proposed. The stability of the overall system is ensured via rigorous stability analysis where asymptotic position tracking is ensured. Numerical simulation results are presented to demonstrate the efficiency of the proposed controller. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Surface vessel; Positioning control; Tugboats; Robust control